2015
DOI: 10.1055/s-0034-1393725
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned in Scalp Reconstruction and Tailoring Free Tissue Transfer in the Elderly: A Case Series and Literature Review

Abstract: This article aims to demonstrate an individualized approach to an elderly patient requiring scalp reconstruction, to describe the methodology in flap selection, lessons learned, and report outcomes. A retrospective review of a single surgeon's experience of scalp reconstruction (E. D. R.) using free tissue transfer from 2005 to 2011, in patients older than 70 years, was completed. A total of eight patients met the inclusion criteria, five males and three females, with a mean age of 80.4 years (range, 73–92). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
(171 reference statements)
1
13
0
Order By: Relevance
“…The disadvantage of this flap is the color mismatch mainly in old male patients. To best of our knowledge, only Sosin has previously reported only a single case of TDAP flap soft‐tissue coverage in cranioplasty; we reported the largest case series (Sosin, Chaudhry, et al, ; Sosin, De la Cruz, et al, ). Taking into account all the benefits and despite few disadvantages, our experience has shown that TDAP flap may be considered as a valuable option in cranioplasty reconstruction.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The disadvantage of this flap is the color mismatch mainly in old male patients. To best of our knowledge, only Sosin has previously reported only a single case of TDAP flap soft‐tissue coverage in cranioplasty; we reported the largest case series (Sosin, Chaudhry, et al, ; Sosin, De la Cruz, et al, ). Taking into account all the benefits and despite few disadvantages, our experience has shown that TDAP flap may be considered as a valuable option in cranioplasty reconstruction.…”
Section: Discussionmentioning
confidence: 73%
“…Sosin already described a case of the TDAP flap for soft tissue reconstruction after cranioplasty (Sosin, Chaudhry, et al, ; Sosin, De la Cruz, et al, ), we present a case series reporting the TDAP flap in cranioplasty reconstruction.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations